(untitled) (ModaPalavra e-periódico, 2025)
For a long time, fashion and the fashion system have been discus-sed as productions of capitalist white supremacist Western culture (hooks, 2019), and we can add patriarchal, cissexist, cishetero-normative, and ciscolonial (Vergueiro, 2016) provocations. This study aims to highlight the importance of Afrodiasporic and de-colonial perspectives to tension the field of fashion, especially the relationship between aesthetics, body, fashion and processes of subjectivation. Considering the importance of embodied and situa-ted perspectives (Kilomba, 2019; Haraway, 1995), this study is a basic research with bibliographic review for affirmative knowledge in developing a critical and sensitive understanding of fashion, the fashion system, and aesthetics. It highlights the contributions of Black Feminisms, Decolonial Theory, Transfeminism, and discus-sions on Fashion and Decoloniality. Thus, in honor of the efforts of Black women and Afro-diasporic perspectives, it proposes the valorizationof black subjectivities as well as ancestry, enabling reflections with embodied perspectives in the fashion field regar-ding processes of subjectivation and the body, as well as culture and aesthetics from the contributions of Black subjectivities. It was possible to understand that the field of fashion is political, that aesthetics are political, as well asdevices for the production of existences, ways of being, being and making the world.